Game model to improve motor skills through traditional sports: Development study on elementary school students - Yusroni, Moh (Universitas Tanjungpura, 2024)
Background and Study Aim. Physical education is a mandatory subject at school which aims to improve students' physical fitness and motor skills to support student activities at school. In elementary school, physical education activities are carried out in a fun way and in the form of games. This research aims to develop a game model that aims to improve the motor skills of elementary school students through traditional sports.Material and Methods. The game model developed integrates various traditional sports that are rich in cultural values and require various motor skills. This research uses the Research & Development (R&D) method. The subjects in this research were elementary school students in Sidoarjo City. The stages in this research are: needs analysis, expert evaluation, small group trials, and large group trials. The data analysis technique in this research uses a quantitative approach with a quasi-experimental method, involving a pretest-posttest control group design to compare the effectiveness of game models on elementary school students' motor skills.Results. The research results showed that this game model succeeded in significantly improving students' motor skills, as well as increasing their interest and participation in sports activities. The effectiveness test of this development product is based on the assessment of 3 motor development experts. The value obtained was 87.% which was declared valid and suitable for use.Conclusion. Based on the development results, it can be concluded: (1) Can be used as a reference to improve students' motor skills. (2) The resulting model has several variations using traditional games. (3) This game model will increase children's interest in participating, because it is a fun game. (4) Participate in preserving national culture, especially traditional games.